On the Move to Meaningful Internet Systems 2007: CoopIS, DOA, ODBASE, GADA, and IS
DOI: 10.1007/978-3-540-76843-2_36
|View full text |Cite
|
Sign up to set email alerts
|

Toward Sound-Assisted Intrusion Detection Systems

Abstract: Network intrusion detection has been generally dealt with using sophisticated software and statistical analysis, although sometimes it has to be done by administrators, either by detecting the intruders in real time or by revising network logs, making this a tedious and timeconsuming task. To support this, intrusion detection analysis has been carried out using visual, auditory or tactile sensory information in computer interfaces. However, little is known about how to best integrate the sensory channels for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…Researchers have reported the ability to hear attacks using a range of mappings from network traffic features to parameters of sound [5], [28]. Qi et al mapped network-traffic parameters to sound, and stated that a range of attack scenarios were distinguishable [28].…”
Section: Sonification For Network-security Monitoringmentioning
confidence: 99%
See 2 more Smart Citations
“…Researchers have reported the ability to hear attacks using a range of mappings from network traffic features to parameters of sound [5], [28]. Qi et al mapped network-traffic parameters to sound, and stated that a range of attack scenarios were distinguishable [28].…”
Section: Sonification For Network-security Monitoringmentioning
confidence: 99%
“…Researchers have reported the ability to hear attacks using a range of mappings from network traffic features to parameters of sound [5], [28]. Qi et al mapped network-traffic parameters to sound, and stated that a range of attack scenarios were distinguishable [28]. Ballora et al sonified network traffic with a view to aiding anomaly detection, and reported the ability to hear patterns associated with port-scanning and distributed denial-of-service (DDoS) attacks [5].…”
Section: Sonification For Network-security Monitoringmentioning
confidence: 99%
See 1 more Smart Citation
“…people with a music background) [19] or experts in the application domain, such as computer network experts [8,13,20]. Therefore mapping strategies generally leverage users' advanced knowledge or ability to detect sound qualities to provide a rich output that displays multiple data dimensions at the same time, associating each of them to different audio synthesis parameters such as pitch, loudness, duration and timbre.…”
Section: Chi 2010: Sensingmentioning
confidence: 99%
“…The Peep [8] and NeMoS [13] systems provide a framework for associating different network traffic conditions and events to the generation of sound, while Qi and others [20] focus on intrusion detection and denial-of-service attacks. All of them differ from what we propose in the present paper in that they are targeted at advanced users -network administrators-rather than nonexperts.…”
Section: Chi 2010: Sensingmentioning
confidence: 99%